2016
DOI: 10.1515/orhu-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Parental care by Black-backed Woodpeckers in burned and unburned habitats of eastern Canada

Abstract: Nest care is an important parental contribution to offspring. In woodpeckers, males often have an equal or greater contribution to parental care, including nest sanitation. The Black-backed Woodpecker (Picoides arcticus) is a North American boreal woodpecker for which both parents are highly involved in parental care. By modifying their territory size in optimal and suboptimal habitat (e.g. burned vs unburned habitats), this species seems to have a large tolerance to variation in prey abundance at a landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…High-severity fires create relatively high initial prey availability and are reported to be particularly important for Black-backed Woodpeckers (Smucker et al 2005, Hanson and North 2008, Hutto 2008, whereas other disturbance types such as widespread beetle infestations do not provide the same magnitude of resource (Bonnot et al 2008, Tingley et al 2020. Tremblay et al (2016) found that both male and female Black-backed woodpeckers had higher food delivery rates and spent less time at the nest per delivery in burned forests compared to green forests, which suggests that greater effort may be needed to raise young in green forests. Forests in our study area did not have recent fire or beetle damage, and we assumed they would have fewer prey resources, which would lead to lower occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…High-severity fires create relatively high initial prey availability and are reported to be particularly important for Black-backed Woodpeckers (Smucker et al 2005, Hanson and North 2008, Hutto 2008, whereas other disturbance types such as widespread beetle infestations do not provide the same magnitude of resource (Bonnot et al 2008, Tingley et al 2020. Tremblay et al (2016) found that both male and female Black-backed woodpeckers had higher food delivery rates and spent less time at the nest per delivery in burned forests compared to green forests, which suggests that greater effort may be needed to raise young in green forests. Forests in our study area did not have recent fire or beetle damage, and we assumed they would have fewer prey resources, which would lead to lower occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, variation in our measured habitat covariates may not have been sufficient to reveal an effect of burn severity, as previously described for Black‐backed Woodpeckers (Tremblay et al. 2016). These woodpeckers likely seek out high‐quality habitats for nesting and foraging, which can limit detection of habitat‐based effects (Stillman et al.…”
Section: Discussionmentioning
confidence: 95%
“…However, some investigators have found that females provision nestlings more frequently than males (Kilham 1966, Short 1974), whereas others have reported no differences between the sexes (Tremblay et al. 2016). In boreal forests in Quebec, provisioning rates of Black‐backed Woodpeckers were lower in unburned than in burned forests, reflecting the need for greater foraging effort in unburned areas and potential negative effects on nestling survival (Tremblay et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations